T Cell Immunosenescence in Aging, Obesity, and Cardiovascular Disease - Kohsuke Shirakawa; Motoaki Sano (Cells, 2021)
Although advances in preventive medicine have greatly improved prognosis, cardiovascular disease (CVD) remains the leading cause of death worldwide. This clearly indicates that there remain residual cardiovascular risks that have not been targeted by conventional therapies. The results of multiple animal studies and clinical trials clearly indicate that inflammation is the most important residual risk and a potential target for CVD prevention. The immune cell network is intricately regulated to maintain homeostasis. Ageing associated changes to the immune system occurs in both innate and adaptive immune cells, however T cells are most susceptible to this process. T-cell changes due to thymic degeneration and homeostatic proliferation, metabolic abnormalities, telomere length shortening, and epigenetic changes associated with aging and obesity may not only reduce normal immune function, but also induce inflammatory tendencies, a process referred to as immunosenescence. Since the disruption of biological homeostasis by T cell immunosenescence is closely related to the development and progression of CVD via inflammation, senescent T cells are attracting attention as a new therapeutic target. In this review, we discuss the relationship between CVD and T cell immunosenescence associated with aging and obesity.